PpSP32-like protein as a marker of human exposure to Phlebotomus argentipes in Leishmania donovani foci in Bangladesh - Sumova, Petra; Sanjoba, Chizu; Willen, Laura; Polanska, Nikola; Matsumoto, Yoshitsugu; Noiri, Eisei; Paul, Shyamal Kumar; Ozbel, Yusuf; Volf, Petr (International journal for parasitology, 2021)
Phlebotomus argentipes is a predominant vector of Leishmania donovani, the protozoan parasite causing visceral leishmaniasis in the Indian subcontinent. In hosts bitten by P. argentipes, sand fly saliva elicits the production of specific anti-salivary protein antibodies. Here, we have utilised these antibodies as markers of human exposure to P. argentipes in a visceral leishmaniasis endemic area in Pabna district, Bangladesh. The use of whole salivary gland homogenate as an antigen to detect these antibodies has several limitations, therefore it is being superseded by the use of specific recombinant salivary proteins. We have identified three major P. argentipes salivary antigenic proteins recognised by sera of bitten humans, expressed them in a recombinant form (rPagSP04, rPagSP05 and rPagSP06) and tested their applicability in ELISA and immunoblot. One of them, PpSP32-like protein rPagSP06, was identified as the most promising antigen, showing highest resemblance and correlation with the IgG response to P. argentipes salivary gland homogenate. Furthermore, we have validated the applicability of rPagSP06 in a large cohort of 585 individuals and obtained a high correlation coefficient for anti-rPagSP06 and anti-P. argentipes saliva IgG responses. The anti-rPagSP06 and anti-P. argentipes salivary gland homogenate IgG responses followed a similar right-skewed distribution. This is the first report of screening human sera for anti-P. argentipes saliva antibodies using recombinant salivary protein. The rPagSP06 was proven to be a valid antigen for screening human sera for exposure to P. argentipes bites in a visceral leishmaniasis endemic area.
Keywords: Bangladéš; Humans; Salivary Proteins and Peptides; Leishmania donovani; hmyzí proteiny; Phlebotomus; Marker of exposure; slinné proteiny a peptidy; lidé; zvířata; Saliva; Phlebotomus argentipes; kousnutí a bodnutí; sliny; IgG antibodies; Bites and Stings; Salivary glands; Animals; Bangladesh; Insect Proteins